Cointegration relationship between carbon price and its factors: evidence from structural breaks analysis. (December 2017) - Zhao, Xuelian; Zou, Yu; Yin, Jiuli; Fan, Xinghua
Abstract: It matters for China to participate in the global "carbon market club" as it is the world's largest emitter of greenhouse gases and soon be the host of the world's largest carbon market. Since 2013, China has announced seven Emissions Trading Scheme (ETS) pilots and will establish a nation wide emission trading market in 2017. This paper studies the long-run relationship between carbon price in Chinese ETS pilots and its influential variables: coal price, economy, temperature and carbon price in European market. Due to existence of structural breaks in every variable, cointegration approaches that consider for one and two structural breaks are applied. Results show that there is a long-run cointegration relationship between carbon price and its factors. The cointegration model with structural breaks outperforms conventional conintegration ones in that it can better explain the actual relationship. Except for the economy variable in Shanghai, all variables play a significant role on carbon price, among which coal price is the dominant factor.